An Automated guided model for merging news into Stock Trading Strategies (International Journal of Engineering and Computer Science, 2015)
The proposed automated model represents merging news into stock trading strategies using genetic programming. Events are retervied from news in free text. The introduced model can be tested by deriving trading strategies based on technical indicators and impacts of extracted events. The trading strategies take the form of system that combine technical indicators with a news variable and revealed through the use of genetic programming. The news variable contains in the best trading policy, indicating the added value of news for predictive purposes and validating our proposed model for automatically merging news in stock trading strategies.